Some Modified Fixed Point Results in V-Fuzzy Metric Spaces - Vishal Gupta; Manu Verma; Mohammad Saeed Khan (Advances in Fuzzy Systems)
The present research paper focuses on the existence of fixed point in V-fuzzy metric space. The presentation of V-fuzzy metric space in n-tuple encourages us to define different mapping in the symmetric V-fuzzy metric space. Here, the properties of fuzzy metric space are extended to V-fuzzy metric space. The introduction of notion for pair of mappings (f,g) on V-fuzzy metric space called V-weakly commuting of type Vf and V-R weakly commuting of type Vf is given. This proved fixed point theorem in V-fuzzy metric space employing the effectiveness of E.A. property and CLRg property. For the justification of the results, some examples are illustrated.